The digital dilemma: Corporate digital transformation and default risk - Wu, Kai; Lu, Yufei (Journal of Financial Stability, 2025)
This study investigates the association between corporate digital transformation and default risk for a sample of Chinese-listed firms from 2009 to 2022. We find a robust positive association between digital transformation and corporate default risk. Further tests reveal the destabilizing impact of digital adoption strengthens under greater competition, human capital intensity, shareholder expropriation, and weak monitoring. The additional analysis points to resource misallocation and managerial manipulations as two potential channels propagating distress. We show that digital transformation correlates with escalated asset impairments and financial frauds. Our study provides evidence that digital transformation strategies entail underappreciated risks to financial stability.